Nisin a probiotic bacteriocin mitigates brain microbiome dysbiosis and Alzheimer’s disease-like neuroinflammation triggered by periodontal disease - Chuanjiang Zhao; Ryutaro Kuraji; Changchang Ye; Li Gao; Allan Radaic; Pachiyappan Kamarajan; Yoshimasa Taketani; Yvonne L. Kapila (Journal of Neuroinflammation, 2023)
Abstract Introduction Periodontitis-related oral microbial dysbiosis is thought to contribute to Alzheimer's disease (AD) neuroinflammation and brain amyloid production. Since probiotics can modulate periodontitis/oral dysbiosis, this study examined the effects of a probiotic/lantibiotic, nisin, in modulating brain pathology triggered by periodontitis. Methods A polymicrobial mouse model of periodontal disease was used to evaluate the effects of this disease on brain microbiome dysbiosis, neuroinflammation, Alzheimer’s-related changes, and nisin’s therapeutic potential in this context. Results 16S sequencing and real-time PCR data revealed that Nisin treatment mitigated the changes in the brain microbiome composition, diversity, and community structure, and reduced the levels of periodontal pathogen DNA in the brain induced by periodontal disease. Nisin treatment significantly decreased the mRNA expression of pro-inflammatory cytokines (Interleukin-1β/IL-1 β, Interleukin 6/IL-6, and Tumor Necrosis Factor α/TNF-α) in the brain that were elevated by periodontal infection. In addition, the concentrations of amyloid-β 42 (Aβ42), total Tau, and Tau (pS199) (445.69 ± 120.03, 1420.85 ± 331.40, 137.20 ± 36.01) were significantly higher in the infection group compared to the control group (193.01 ± 31.82, 384.27 ± 363.93, 6.09 ± 10.85), respectively. Nisin treatment markedly reduced the Aβ42 (261.80 ± 52.50), total Tau (865.37 ± 304.93), and phosphorylated Tau (82.53 ± 15.77) deposition in the brain of the infection group. Discussion Nisin abrogation of brain microbiome dysbiosis induces beneficial effects on AD-like pathogenic changes and neuroinflammation, and thereby may serve as a potential therapeutic for periodontal–dysbiosis-related AD.